Production Of Biogas From Anaerobic Digestion Of Poultry Droppings And Domestic Waste Using Catalytic Effect Of Silica Gel - Ahamed, J. U.; Raiyan, M. F.; Hossain, MD. S.; M. M., Rahman; Salam, B. (Universiti Malaysia Pahang, 2016)
This research work has been performed to produce biogas from poultry and household (kitchen) waste using silica gel as a catalyst. A fabricated laboratory scale digester was used to generate biogas from the locally available waste obtained from poultry farms and domestic kitchens. Two laboratory-scale digesters were prepared to digest the solid wastes with and without silica gel respectively. The operating temperatures of the digesters were maintained within 26°C-31°C. The water displacement method was used to investigate the volume of the produced gas. It was found that the production rate of biogas was increased while using silica gel as catalyst. The total gas production was found to be 7921 ml/kg of waste without silica gel whereas it was 10545 ml/kg with a maximum production rate of 1206 ml/kg in a day with silica gel as a catalyst and it was 33.12% higher than before. Finally, by using a k-type thermocouple, the flame temperature of the gas was measured as 619°C. Considering the magnitude of flame temperature and total gas yield after adding the silica gel, the large scale set-ups can be a prospective source of clean energy